Microbial quality of drinking water in Dar es Salaam and use of Waterguard&#174 as disinfectant (Tanzania Medical Journal, 2007)
Water borne diseases are alarmingly high in urban areas like Dar es Salaam. Hence the importance of chlorine-based water disinfectant solutions such as Waterguard&#174 that consists of 0.75% sodium hypochlorite. Waterguard&#174 has been in the market in Dar es Salaam for about 4 years. Despite this, prevalence of waterborne diseases like cholera, dysentery and typhoid are still high. The aim of this study was to investigate the effectiveness of Waterguard&#174 in disinfecting drinking water, and determine the level of fecal coliform contamination of water from four sources viz. taps, streams, shallow wells and deep wells located within Dar es Salaam city. The investigation on the efficacy of the agent was carried out in water samples collected in the city during a 4-month period. Sixty-four water samples were randomly collected and analyzed by the Most Probable Number (MPN) technique based on coliform counts for both untreated and treated water samples. Negative (distilled water) and positive (distilled water contaminated with feces) controls were also included. Results show that three out of the four water sources were heavily contaminated with the exception of deep wells. But appropriate use of Waterguard&#174 reduces the level of microbial contamination significantly. In this study the assayed Waterguard&#174 was found to be 100% efficacious in treating the samples to a level within the WHO safety standards, hence is fit for disinfecting water for human use. Keywords: Drinking water quality, Coliform Contamination, Waterguard. Tanzania Medical Journal Vol. 21 (1) 2006: pp. 22-24